Allocation of Special Drawing Rights For The Eleventh Basic Period : Draft Executive Board Decision and Managing Director Report to the Board of Governors. (Policy Papers; Policy Paper ;, 2021)
On June 25, 2021, the Executive Board discussed a staff paper setting forth the considerations underlying the case for a general allocation of special drawing rights (SDRs) of an amount equivalent to USD 650 billion (about SDR 456 billion) during the Eleventh Basic Period and the key features that could be included in the Managing Director's proposal for this general allocation.